(untitled) (Journal of actual problems of jurisprudence, 2019)
In given article the author considers the criminal liability of legal bodies in the foreign legislation of some countries. Besides, investigates necessity of attraction of legal bodies to the criminal liability under the Republic Kazakhstan criminal code.